Psychosocial interventions for very early and early-onset schizophrenia. Issue 4 (July 2015) - Armando, Marco; Pontillo, Maria; Vicari, Stefano
<x xml:space="preserve">Abstract</x> Purpose of review Very early (VEOS) and early-onset schizophrenia (EOS) represent more severe forms of the disorder, with clear differences from adult-onset schizophrenia (AOS). However, there is a distinct lack of evidence regarding the efficacy of psychosocial interventions in this group of patients, and to date no systematic review has been conducted on the topic. The aim of this article is to review the current knowledge and evidence on the efficacy of psychosocial interventions in VEOS/EOS. Recent findings A total of eight articles were eligible for inclusion. Four studies evaluated psychoeducational and family interventions for patients with VEOS/EOS, whereas four studies focused on cognitive behavioral therapy or cognitive remediation. Overall, we found some preliminary evidence for the efficacy of psychosocial interventions in the treatment of VEOS/EOS. This evidence was strongest for cognitive remediation. Summary Heretofore, VEOS/EOS have been treated primarily with psychosocial interventions based on evidence from interventions tailored for and tested on adults. Although more conclusive studies are still needed, thanks to recent clinical trials, we now have greater evidence to support the efficacy of psychosocial interventions in EOS/VEOS.